Filología arqueoibérica: cuestión de método (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The present state of Archaeo–Iberian Philology, which we consider rather worrying in some respects, encourages us to formulate a series of considerations about the methodology and procedures of this growing discipline.
Keywords: Iberian; Celtiberian; Methodology; Epistemology; texts